Peran Keluarga dalam Mendidik Anak Menurut Abdurrahman An Nahlawi - Rachmawati, Ulli Tiyas; Khariroh, Ummi; Basuki, Basuki (Graduate School of Universitas Negeri Malang, 2024)
Family education places the responsibility of parents as the first educators. The family environment is the smallest unit in society because children from birth to adulthood are educated in the family. The purpose research is to examine the influence and role of parents in educating children so that character to build character. The research method is a literature review that uses two sources, namely the primary source of the book Usul at-Tarbiyyah Al-Islamiyyah wa Asalibiha fi al-Bait wa al-Madrasah wa al-Mujtama'. Research procedures with data input, data processing, data analysis and conclusions. The results of the research is upholding the laws of Allah SWT, realizing peace of mind, carrying out the orders of Prophet Saw, realizing love for children and maintaining the nature of the child from immersion and deviation.